Prevalence and Risk Factors of Intradialytic Complications among End-Stage Kidney Disease Patients on Maintenance Hemodialysis in Central Nepal - Sharma , Deepak; Maharjan, Chunumila; Ghimire, Madhav (Journal of College of Medical Sciences-Nepal, 2025)
Background Intradialytic complications remain a significant barrier to quality care in maintenance hemodialysis (MHD), particularly in resource-limited settings. This study aimed to evaluate the prevalence of intradialytic complications and their association with clinical factors among end-stage kidney disease (ESKD) patients undergoing MHD in a tertiary hospital in Nepal. Methods We conducted a hospital-based observational study involving 143 ESKD patients receiving MHD from July 2020 to September 2021. Data on demographics, clinical history, dialysis parameters, and intradialytic events were collected using a structured proforma. Statistical analysis assessed associations between intradialytic complications and factors including diabetes, hypertension, dialysis duration, and food intake during sessions. Ethical approval was obtained from the Institutional Review Committee (Ref. No. 2020-097; Date: November 20, 2020). Results Intradialytic complications were observed in 61.5% of patients. The most common was intradialytic hypertension (39.9%), followed by hypotension (14.7%) and headache (14.7%). Chest pain (9.1%), nausea (10.5%), and vomiting (4.9%) were also reported. Intradialytic hypertension was more frequent among patients with diabetes (53.3%) and hypertension (17.6%). It was also more common among patients with dialysis duration <1 year or >5 years, and among those who consumed food during dialysis. Conclusions Intradialytic complications were prevalent, with hypertension being the most common. Diabetes, hypertension, dialysis duration, and intradialytic food consumption were significant contributors.